Given $X\sim U(1, 0)$ and $Y\sim Exp(1)$, determine the density function of $Z:=\frac{X}{Y}$.

Now, without looking up how to do it I tried to figure it out myself.

The value of the density function $f_X(x)$ is the continuous analog of the probability that $X=x$, right? I realize that $\mathbb P(X=x)=0$ fore every $x$, but it seemed so far that reasoning about random variables this way produced correct results. Also, the continuous analog of a sum is an integral.

Now, $f_Z(z)=f_\frac{X}{Y}(z)$. There is an infinite number of ways that the quotient of $X$ and $Y$ could produce $z$ so I integrated over all of them like this $\int_{-\infty}^{+\infty}f_X(x)f_Y(x/z)dx$. Now, since $f_X$ is zero everywhere but on $[0,1]$ where it's one, the integral becomes $\int_0^1f_Y(x/z)dx=z(1-e^{-1/z})$. This all seemed logical to me but then I tried the reverse. Integrating over the possible values of $Y$ and then making $X$ match them.


Why doesn't this give the same result? I'm really hoping that I didn't just make a simple calculation mistake. Actually, maybe I'm hoping I did just that so my method can be salvaged.

I would appreciate any insight.

  • $\begingroup$ What is B(1,0)? B is for Beta, Bradford, Binomial, Birnbaum, Bettyboop ... $\endgroup$ – wolfies Apr 28 '15 at 11:06
  • $\begingroup$ @wolfies Oh sorry. That was supposed to be $U$. For uniform. $\endgroup$ – Luka Horvat Apr 28 '15 at 11:06

The ratio distribution is evaluated by the integral: $$\begin{align} f_Z(z) & = f_{X/Y}(z) \\ & = \int_\Bbb R \lvert y\rvert f_X(yz)f_Y(y)\operatorname d y \\ & = \int_0^{1/z} y e^{-y} \operatorname d y \\ & = 1-e^{-1/z} (\tfrac 1 z + 1) \end{align}$$

Going back to first principles.

$\begin{align} P(Z\leq z) & = P(X \leq Yz) \\ & = \int_0^\infty\int_{0}^{\min(yz,1)} e^{-y}\operatorname d x\operatorname d y \\ & = \int_0^{1/z} e^{-y}\int_0^{yz} 1\operatorname d x\operatorname d y + \int_{1/z}^\infty e^{-y}\int_0^1 1\operatorname d x\operatorname dy \\ & = z\int_0^{1/z} ye^{-y}\operatorname d y + \int_{1/z}^\infty e^{-y}\operatorname dy \\ & = \left(z-e^{-1/z} (z+1)\right) +\left(e^{-1/z}\right) \\ & = z(1-e^{-1/z}) \\[2ex] f_Z(z) & = \frac{\mathrm d}{\mathrm d z}\Big(P(Z\leq z)\Big) \\ & = 1-(1+\tfrac 1 z)e^{-1/z} \end{align}$

In general, when $X>0,Y>0$: $$\begin{align}f_Z(z) & = \frac{\mathrm d}{\mathrm d z} \int_0^\infty\int_0^{yz} f(x,y)\operatorname d x\operatorname d y \\ & = \int_0^\infty y f(zy,y)\operatorname d y\end{align}$$

| cite | improve this answer | |
  • $\begingroup$ Can you point out what's wrong with my reasoning above? $\endgroup$ – Luka Horvat Apr 28 '15 at 12:55
  • $\begingroup$ It seems like the formula is what I had in my second attempt with the extra $|y|$ in it. Is there an intuitive explanation? $\endgroup$ – Luka Horvat Apr 28 '15 at 12:56
  • $\begingroup$ Does this help? @LukaHorvat $\endgroup$ – Graham Kemp Apr 29 '15 at 5:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.